Pengaruh Free Cash Flow Dan Economic Value Added Terhadap Return Saham(Studi pada Saham Perusahaan yang Tercatat Aktif dalam LQ 45di BEI Periode 2015-2017) - Fedro Christian Montoliang; Lauw - Tjun Tjun (Jurnal Akuntansi, 2018)
This study aims to analyze the effect of free cash flow and economic value added on stock returns. The type of data used is primary data and secondary data. The sample used is a company that is listed active in LQ 45 in BEI Period 2015-2017. Methods of data analysis using multiple regression analysis. Data processing is done by using SPSS Version 20 for windows. The results showed that there is a significant effect between free cash flow with stock return, there is a significant influence between economic value added with stock return, and there is significant influence between free cash flow and economic value added simultaneously with stock return.Â Keywords: Economic Value Added, Free Cash Flow, Stock Return, and Stock